Perbandingan Pendidikan Politik Partai Golkar dalam Meningkatkan Perolehan Suara pada Pemilu 2019 dan 2024 - Nur Habibah, Salma Zulfa; Tsabitah Aldjabri, Rachel Hisanaah; Ayu, Nia Rafa; Susilo, Galang Putra; Hanifan, Hafiz Zaki (Prodi Ilmu Politik, 2025)
This study compares the role of political education conducted by the Golkar Party in increasing vote acquisition during the 2019 and 2024 general elections. It employs a descriptive qualitative method, using primary data from interviews with internal Golkar Party sources and secondary data from literature reviews. The findings show that in the 2019 election, Golkar’s political education remained conventional, elitist, and limited in scope. In contrast, the 2024 election saw the adoption of more modern and participatory strategies, including the use of social media, the establishment of the Golkar Institute, and collaboration with the General Elections Commission (KPU) through the